Site- and enantioselective B−H functionalization of carboranes - Kyungsup Lee; Gisela A. González-Montiel; Hyeonsik Eom; Tae Hyeon Kim; Hee Chan Noh; Abdikani Omar Farah; Henry R. Wise; Dongwook Kim; Paul Ha-Yeon Cheong; Phil Ho Lee (Nature Communications)
Abstract Functionalization of carboranes, icosahedral boron−carbon molecular clusters, is of great interest as they have wide applications in medicinal and materials chemistry. Thus, site- and enantioselective synthesis of carboranes requires complete control of the reaction. Herein, we describe the asymmetric Rh(II)-catalyzed insertion reactions of carbenes into cage B–H bond of carboranes. This reaction thereby generates carboranes possessing a carbon-stereocenter adjacent to cage boron of the carborane, in excellent site- and enantioselectivity under mild reaction conditions. The fully computed transition structures of Rh(II)-catalyzed carbene insertion process through density functional theory are reported. These B–H insertion transition structures, in conjunction with topographical proximity surfaces analyses, visually reveal the region between the carborane and the phthalimide ligands responsible for the selectivities of this reaction.